Advances in liquid crystals. - Brown, Glenn H. (Glenn Halstead) (Advances in Liquid Crystals, 1975)
Advances in Liquid Crystals, Volume I is a collection of papers dealing with lyotropic and thermotropic liquid crystals. One paper discusses lyotropic liquid crystalline phases in systems of amphiphilic compounds, including the liquid crystalline phases, lyotropic liquid crystalline phase, the """"gel"""" phases, and the transition between normal and reversed mesophases. Another paper describes the ordering and structure of liquid crystals by reviewing research work on X-ray analysis of thermotropic liquid crystals. One paper explains the studies made on the mesomorphic behavior of block copo